Improving the measurement of food security - Headey, Derek D.; Ecker, Olivier (International Food Policy Research Institute, 2012)
Although food security measurement has been substantially expanded in recent decades, there persists significant dissatisfaction with existing measurement systems, especially in the wake of the global food and financial crisis. In this paper we first set out a list of criteria that an ideal food security measurement system should satisfy. We then benchmark existing indicators and measurement systems against those criteria as a means of systematically identifying their relative strengths and weaknesses. Our concluding section outlines possible steps for improving food security measurement through a mixture of extension, coordination, and innovation.